Relationship between circadian rhythm characteristics and chronotypes with multiple sclerosis: literature review - Jonušaitė, Ieva; Sakalauskaitė-Juodeikienė, Eglė; Mameniškienė, Rūta; Kizlaitienė, R. (Neurologijos seminarai, 2021)
Circadian rhythm disorder is described as discrepancy between person’s sleep habits and usual, generally accepted sleep model during 24-hour period. Circadian rhythm disorders affect not only person’s working capacity during the day but also may reduce quality of life. The term chronotype refers to a specific circadian rhythm manifestation – person’s preference to sleep and to be awake at some point of 24-hour period. Both circadian rhythm disorders and increased serum levels of proinflammatory cytokines are considered as factors negatively affecting sleep homeostasis among patients with multiple sclerosis. It is important to recognize and manage circadian rhythm variations and associated sleep disorders among patients with multiple sclerosis in order to reduce fatigue, improve cognitive functions and mood, and general quality of life. In this review article, we describe mechanism of action of circadian rhythm, its imbalances, objective and subjective evaluation methods of circadian rhythm and chronotypes, as well as relationship between circadian rhythm characteristics, chronotypes, melatonin concentration, oxidative stress, and multiple sclerosis.
Keywords: circadian rhythm; chronotype; multiple sclerosis; melatonin; oxidative stress